PENGARUH MODEL PEMBELAJARAN MIND MAPPING BERBANTUAN VIDEO TERHADAP PEMAHAMAN KONSEP SISWA KELAS 2 MI GEDANGANAK: PENGARUH MODEL PEMBELAJARAN MIND MAPPING BERBANTUAN VIDEO TERHADAP PEMAHAMAN KONSEP SISWA KELAS 2 MI GEDANGANAK - Putri Yuniarsih; Lisa Putra (STKIP Subang, 2024)
ABSTRACT Basically, education is an individual process in developing one's own potential and facing the changes that are occurring. There are many societal challenges in the ongoing social developments regarding the quality of education in this country. Learning which basically aims to direct children in achieving learning goals as planned. From this approach there will be differences or gaps between smart children and less intelligent children in achieving learning goals. This condition makes it difficult to achieve the fulfillment of Learning Objectives. A learning strategy that can be used as an example is an Active Learning Strategy. The low ability of students to understand concepts is of course related to the learning implementation process. Students' thinking also becomes less clear because students are not optimally involved in the learning process. Lack of learning in groups also encourages student individualism, so that students cannot work together in teams or groups. Thus, the objectives of this research are as follows: (1) To determine differences in students' understanding of concepts after using the video-assisted Mind Mapping learning model in Class II MI Gedanganak students. (2) To determine the effect of using the video-assisted mind mapping learning model on students' understanding of concepts in class II MI Gedanganak. This research uses quantitative methodology and uses experimental research, which aims to determine the differences between the experimental class and the control class. Where Hypothesis Test I was carried out using the Independent Sample T-Test. The learning model used by researchers is Mind Mapping with video media, and the sample from this study is class 2 students at MI Gedanganak. At the end of the learning activity, the researcher gave a post-test to determine the difference between the experimental class which used the Video-assisted Mind Mapping Learning Model, and the control class which only used the Mind Mapping Learning Model. The following is a post-test result comparing the averages of the two classes which will later be tested using the Independent Sample T-Test. type of understanding Sub Indicator Class Average 2A (Experiment) 2B (Control) Concept Understanding Interpretation 95% 98% 96,5% Identify 96% 91% 93,5% Classifying 84% 84% 84% Compare 56% 48% 52% Drawing Inferences 94% 87% 90,5% Summarizing 80% 52% 66% Interpret 78% 66% 72% Total 83,28% 75,14% 79,21%